Microscopic hematuria is a risk factor for end-stage kidney disease in patients with biopsy-proven diabetic nephropathy. Issue 2 (4th November 2020) - Okada, Sadanori; Samejima, Ken-ichi; Matsui, Masaru; Morimoto, Katsuhiko; Furuyama, Riri; Tanabe, Kaori; Eriguchi, Masahiro; Akai, Yasuhiro; Saito, Yoshihiko; Tsuruya, Kazuhiko
Abstract : Introduction: There are fewer reports about whether the presence of hematuria affects the progression of chronic kidney disease in patients with diabetic nephropathy. We analyzed whether microscopic hematuria in diabetic nephropathy is a risk factor for end-stage kidney disease (ESKD). Research design and methods: The present study was a retrospective cohort study of patients with biopsy-proven diabetic nephropathy. We recruited 397 patients with diabetic nephropathy, which was confirmed by renal biopsy between June 1981 and December 2014 and followed them until October 2018 or death. Patients with microscopic hematuria before renal biopsy were defined as the hematuria group (n=91), and the remainder as the no-hematuria group (n=306). The main outcome was the occurrence of ESKD, which was defined by the requirement of permanent renal replacement therapies. Results: The systolic and diastolic blood pressure, serum creatinine and proteinuria were significantly higher, and the estimated glomerular filtration rate was significantly lower in the hematuria group compared with the no-hematuria group. Pathological evaluations revealed that glomerular, tubulointerstitial and vascular lesions in the hematuria group were significantly more severe. During a median of 10.1 years, 44 and 52 patients developed ESKD in the hematuria group and the no-hematuria group, respectively. Survival analyses showed that the incidence of ESKD was significantly higher in the hematuria group compared with the no-hematuria group (log-rank, p<0.0001). The multivariable Cox proportional hazards models revealed a significant association between hematuria and the incidence of ESKD after adjusting for clinically relevant factors, including proteinuria and renal pathology (adjusted HR 1.64, 95% CI 1.03 to 2.60). The subgroups of men, proteinuria ≥0.5 g/day, and systolic blood pressure ≥132 mm Hg showed a stronger association between hematuria and ESKD than their opposing subgroups. Conclusions: Microscopic hematuria is a risk factor for ESKD in diabetic nephropathy, independent of proteinuria and renal pathology.